2012
DOI: 10.1097/shk.0b013e31824653be
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol Attenuates the Severity of Acute Pancreatitis and Associated Lung Injury via Acceleration of Acinar Cell Apoptosis

Abstract: Severe acute pancreatitis remains a life-threatening disease with a high mortality rate among a defined proportion of those affected. Apoptosis has been hypothesized to be a beneficial form of cell death in acute pancreatitis. Honokiol, a low-molecular-weight natural product, possesses the ability of anti-inflammation and apoptosis induction. Here, we investigate whether honokiol can ameliorate severe acute pancreatitis and the associated acute lung injury in a mouse model. Mice received six injections of ceru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…In the present study, honokiol administration significantly decreased the levels of caspase-3 in the IRI rats. Weng et al suggested that honokiol attenuates the severity of acute pancreatitis and lung injury through suppression of apoptosis and caspase-3 activity (44). Honokiol also inhibits the activation of caspase-3 and caspase-9 in H 2 O 2 -induced apoptosis in human lens epithelial cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, honokiol administration significantly decreased the levels of caspase-3 in the IRI rats. Weng et al suggested that honokiol attenuates the severity of acute pancreatitis and lung injury through suppression of apoptosis and caspase-3 activity (44). Honokiol also inhibits the activation of caspase-3 and caspase-9 in H 2 O 2 -induced apoptosis in human lens epithelial cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…In patients and animals with AP, serum levels of HMGB1 are significantly elevated and positively correlate with the severity of this disease (Kocsis et al, 2009; Yasuda et al, 2007; Yasuda et al, 2006). Importantly, inhibiting the release or cytokine activity of HMGB1 (e.g., HMGB1 neutralizing antibody, ethyl pyruvate, danaparoid sodium, cisplatin, A box, antithrombin III, and pyrrolidine dithiocarbamate) confers protection against experimental AP (Cheng et al, 2007; Hagiwara et al, 2009g; Jo et al, 2013; Luan et al, 2013a; Luan et al, 2012; Luan et al, 2013b; Sawa et al, 2006; Weng et al, 2012; Yan et al, 2012a; Yang et al, 2009b; Yang et al, 2008; Yuan et al, 2009; Zhang et al, 2010). However, intracellular HMGB1 in the pancreas protects against acute pancreatitis (Kang et al, 2013b).…”
Section: Hmgb1 and Diseasementioning
confidence: 99%
“…We previously showed that DCQD can ameliorate pancreatic inflammation and pathological damage by inducing a necrosis-apoptosis switch in AR42J cells and a rat model of AP [7]. Other studies similarly reported that treatment with various components of DCQD induces apoptosis and reduces necrosis of acinar cells in AP [8–10]. However, the active components and mechanism underlying this effect remain uncertain.…”
Section: Introductionmentioning
confidence: 99%